Strategies for Strengthening Ethics and Integrity to Prevent Corruption in Indonesia - Said Amirulkamar; Khalida Ulfa; Siti Nur Zalikha; Said Mayzar Mulya; Ummunisa Hidayati; Santi Zuli Yana (Jurnal Ilmu Sosial dan Humaniora, 2023)
Corrupt behavior in Indonesia has existed since the kingdom era. Therefore, a strategy is needed to strengthen ethics and integrity to prevent corruption in Indonesia. The government has also enacted various laws and regulations that serve as guidelines for strengthening the ethics and integrity of government officials to prevent corruption. One is the Law of the Republic of Indonesia Number 28 of 1999 concerning the Administration of a State that is clean and free from corruption, collusion, and nepotism. The research method used is the descriptive qualitative method. The data analysis technique used was the Content Analysis Technique. Nvivo 12 Plus analysis technique uses Crosstab and Sociogram features in data analysis. The Nvivo 12 plus analysis technique is data processing based on the big data obtained. The results of the study show that the strategy that can be used in strengthening ethics and integrity to prevent corruption in Indonesia can be carried out by the government by implementing anti-corruption education in every institution and element of society, which is manifested in various programs and can also be carried out through social media, namely by uploading various acts of corruption. Events around the community can be immediately followed up by law enforcement agencies and through public solid oversight, codes of conduct, and the rule of law.